Efficient text data hiding technique using cryptography and steganography - Mohd Sani, Nor Fazlida; Nujjaid, Mohamad Adreen (Science Publications, 2024)
Steganography serves as a technique for covertly embedding confidential information within other data, ensuring that both the existence and content of this hidden data remain undisclosed to unauthorized parties. Its applications span diverse domains, including military operations, online payment systems, and the Internet of Things (IoT). Steganography proves highly adaptable in concealing data, as information with an unknown presence escapes detection by potential attackers. Nonetheless, recent developments in steganalysis and image processing techniques have made it simpler for adversaries to reveal secret information. In response to this challenge, researchers have suggested various countermeasures, such as integrating steganography with encryption. This study employs steganography utilizing the Least Significant Bit (LSB) approach, which uses the Advanced Encryption Standard (AES) for symmetric encryption, and the Rivest-Shamir-Adleman (RSA) method for asymmetric key encryption. The Diffie-Hellman key exchange method improves the procedure as a whole. The effectiveness of these methods in protecting and hiding confidential information is then evaluated, along with how quickly the data is hidden. According to the results, using Diffie-Hellman key exchange in conjunction with AES performs better than using RSA for the encryption technique in terms of data hiding capabilities and speed.